Análisis de consorcios bacterianos y grupos funcionales asociados a la rizosfera de la papa (Solanum tuberosum). Var super chola en el piso altitudinal de 3800 msnm, Cotopaxi 2021 - Nasimba Chanataxi, Nathalia Belen (2021)
The present investigation was carried out in the altitudinal floor of 3800 meters above sea level in the community of Cuturivi Chico, province of Cotopaxi, with the objective of identifying bacterial consortia and functional groups associated to the rhizosphere of potato crop. For the present investigation, bacterial identification by sequencing of the 16S gene was used; for the functional groups, the methodology of (Bernal, 2005) was used for the determination of the groups mentioned by specific means: Total microbiota using Nutrient Agar, Nitrogen Fixing Bacteria using Watanabe. Phosphorus solubilizing bacteria using Ramos Callao Agar. Fungi using Rose Bengal Agar Actinomycete, Casein Agar was used. Cellulolytic Bacteria using Soil Extract Agar Pseudomonas B de king was used. In addition, to know the state of soil composition, a physical-chemical analysis was carried out in the INIAP laboratory. From the data obtained in the metagenomic analysis, three representative families Enterobacteriaceae, Xanthomonadaceae and Rhodanobacteraceae were identified, of which the most representative genera were Raoultella, Rhodanobacter and the species with the highest abundance were Raoultella ornithinolytica, Raoultella terrigena. The functional groups with the highest representation were phosphorus solubilizing bacteria, actinomycetes and pseudomonads in colonies*gr and cfu*gr respectively.